Conceptual Metaphors of “water” in Javanese Proverbs from a Cognitive Linguistic Perspective - Noviana Fajria (EDP Sciences, 2021)
This paper examines how the Javanese views the concept of water. Water is one of the natural elements whose existence is essential for humans. This study examines Javanese proverbs containing the word “water” or banyu in Javanese through a qualitative paradigm and a cognitive linguistic approach. Data were obtained from the Javanese Proverbs Dictionary by Darmasoetjipta. Proverbs are used as the object of study, considering that proverbs are one of the language products of a culture born based on the experience of human interaction with nature or the world and has been hereditary believed to be one of the guidelines or advice for life. The proverb contains metaphors so that in examining it, this research uses conceptual metaphor theory. Metaphor is not simply a language feature; it is also an embodiment of human nature. Metaphor is an effective cognitive tool to study how the human thinking mechanism is, how humans perceive reality in an image schema, map it in cognition, and express it through language. Based on the data analysis, it was found that water, according to the Javanese, is seen as a conceptualization of ideological values used as guidelines in social behaviour and social relationships.